PERLINDUNGAN ANAK DARI KONTEN BERBAHAYA MEDIA ELETRONIK DIKAITKAN DENGAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Kartini, Murtiningsih (Yustitia, 2019)
Children are the hope of a nation. They are our next generation, and in their hands thefuture of this nation will be laid. As the successor of the nation, it is necessary for thepresent generation to provide protection to them from moral damage caused by the use ofdangerous content in printed and electronic media, especially content that containselements of violence and pornography. This research used normative research methodwhich is based on the study of legal materials from the literature and is as a process tofind the rule of law, legal principles, and legal doctrines in order to answer the contents ofthe law encountered. The legal protection for children and women is indeed an absolutething to be done by the government. They are the institution responsible for the continuityof an orderly, peaceful and prosperous community life. The legislation that regulates thelegal protection of children from dangerous content in printed and electronic media is stillgeneral. There are no specific rules aimed at providing legal protection for children fromdangerous content that might be present in printed and electronic media.